Building the Concept of Siri'na Pacce in The Aspiration of Corporate Social Responsibility - Ari Utomo Saputra; Nengsi Sudirman; Ari Ayu (IECON: International Economics and Business Conference, 2024)
Purpose: This study aims to explore the application of the cultural value of "Siri' Na Pacce" in corporate social responsibility (CSR) in the field of accounting. Motivation: Accounting is now not only about recording as if accounting is like a robot that serves the interests of capital owners and does not care about the surrounding conditions, accounting must be explored by providing benefits to the surrounding environment after exploiting natural resources and human resources. Therefore, accounting must foster a sense of concern for nature in its own way because humans are truly created with full feelings in themselves. Analysis Method: The methodology used is a literature study, with an analysis of the concept of CSR and its relationship to local Bugis-Makassar values, namely shame (Siri') and compassion (Pacce). Findings: The findings show that the integration of these values ​​can encourage more ethical and socially responsible accounting practices because someone who instills this siri' na pacce culture as their identity will be fairer to society and nature itself. Implications: This study has significant potential in enriching CSR literature in Indonesia, as well as strengthening the importance of local ethics in sustainable business policies. Originality/Value: This study provides a deeper understanding of the concept of siri'na pacce which also has practical contributions for companies, local communities, and academic literature that want to combine local wisdom with CSR principles.